2021
DOI: 10.1039/d1lc00131k
|View full text |Cite
|
Sign up to set email alerts
|

A novel human arterial wall-on-a-chip to study endothelial inflammation and vascular smooth muscle cell migration in early atherosclerosis

Abstract: Mechanistic understanding of atherosclerosis is largely hampered by the lack of suitable in vitro human arterial model that recapitulates the arterial wall structure, and the interplay between different cell types...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 57 publications
0
48
0
Order By: Relevance
“…While the dual-lane stepped-height based hydrogel chip have been reported for arterial wall-on-a-chip [ 29 ], we further demonstrated the scalability of this method to pattern multiple adjacent lanes of hydrogel using single or dual stepped heights. An injection-molded culture platform for patterning three adjacent lanes of hydrogel have been reported [ 37 ], but it lacks the flexibility to pattern two different hydrogels for the first two lanes.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…While the dual-lane stepped-height based hydrogel chip have been reported for arterial wall-on-a-chip [ 29 ], we further demonstrated the scalability of this method to pattern multiple adjacent lanes of hydrogel using single or dual stepped heights. An injection-molded culture platform for patterning three adjacent lanes of hydrogel have been reported [ 37 ], but it lacks the flexibility to pattern two different hydrogels for the first two lanes.…”
Section: Discussionmentioning
confidence: 68%
“…Our group previously developed a hydrogel patterning method based on channel stepped heights and capillary burst valve (CBV) effect for blood vessel studies [ 28 , 29 ]. Herein, we further explore the versatility and scalability of the stepped-height based technique for 3D cell cultures in enclosed microchannels and spheroid-in-gel cultures in an open-channel microarray format.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al first reported a microfluidic EC-SMC co-culture device for a normal artery wall model. Then they stimulated the model with pro-inflammatory cytokines (such as TNF-α and IL1-β) and oxidized LDL for studying endothelial inflammation in early atherosclerosis [151]. Furthermore, drug screening was also applied in this model and confirmed that Vitamin D, a drug known as anti-atherogenic, could inhibit monocytes-EC adhesion and SMC migration.…”
Section: Atherosclerosismentioning
confidence: 92%
“…Notably, the SMC migration into the EC layer could be easily quantified using such a system, which cannot be achieved through a traditional transwell assay. Moreover, the potential of this system as a drug screening tool was demonstrated by the atheroprotective effect of vitamin D, and metformin was observed when tested using this model (158). However, the main limitation of this study is that the EC layer is not monolayer and is as thick as the SMC layer, and lacks tunica adventitia.…”
Section: In Vitro 3d Cell-laden Hydrogel Constructsmentioning
confidence: 95%